Pregnancy outcome in long- versus short-acting gonadotropin-releasing hormone agonist cycles in participants with normal ovarian reserve: An RCT - Roya Kabodmehri; Nasrin Ghanami Gashti; Azadeh Raoufi; Marzieh Mehrafza; Zahra Nikpouri; Elmira Hosseinzadeh; Ahmad Hosseini (Shahid Sadoughi University of Medical Sciences, 2023)
Background: There is no agreement on which of the 2 gonadotropin-releasing hormone (GnRH) agonist protocols are the most efficient, neither there is any consensus on which one yields a better clinical pregnancy percentage. Objective: The present study aims to compare the effectiveness of reduced dosages of long- and short-acting GnRH agonists on pregnancy outcomes. Materials and Methods: In this randomized controlled clinical trial, 400 women were randomly assigned to 2 groups (n = 200/group): the reduced dosage of long-acting GnRH agonist group (group 1, 1.25 mg Decapeptyl) and the short-acting GnRH agonist group (group 2, 0.5 mg/day Buserelin Acetate). The study was conducted at Mehr Medical Institute, Rasht, Iran between July 2019 and July 2020. Biochemical and clinical pregnancy were compared between groups. Results: No significant differences were observed in the endometrial lining, the total number of retrieved and metaphase-II oocytes, progesterone, and serum estradiol levels on human chorionic gonadotropin day, fertilization rate, and top-quality embryos between the groups. The duration of induction (10.8 ± 1.7 vs. 10 ± 2.1, p < 0.001) and the total dosage of gonadotropins (2939.4 ± 945.9 vs. 2441 ± 1247.1, p < 0.001) were significantly greater in group 2 than in group 1. No significant differences were observed between the 2 groups in terms of implantation rate, chemical pregnancy rate, and clinical pregnancy rate. A higher percentage of ovarian hyperstimulation syndrome was observed in group 2 (p = 0.005). Conclusion: Due to a lower percentage of ovarian hyperstimulation syndrome in group 1 and similar assisted reproductive technology outcomes in both groups, the long protocol was found to be superior to the short protocol.